Integrating team-based and peer-teaching strategies for standardized dental residency: a path to active learning and professional growth - Leshi Wang; Peiwen Chen; Xiao Wang; Sijia Wei; Jiayi Lin; Xi Jing (BMC Medical Education)
Abstract Background This study aimed to assess the effectiveness of an integrated Team-Based Learning (TBL) and Peer Teaching (PT) model in enhancing theoretical knowledge, clinical competencies, and engagement among dental residents, offering insights for improving stomatology education. Methods This study was conducted at the affiliated stomatology hospital of Guangzhou medical university between 2021 and 2023. The 2021–22 cohort (n = 39) students received a traditional teacher-centered approach, whereas the 2022–23 cohort (n = 43) underwent a combined TBL and PT approach. Following a three-month training period, theoretical exams and OSCE were administered. Student engagement was evaluated using the SCEQ, and satisfaction was assessed through SSS. Data were analyzed using independent t-tests, Mann-Whitney U tests, and χ² tests, with statistical significance set at p < 0.05. Results No significant baseline differences were observed in demographics. TBL + PT cohort demonstrated significantly higher theoretical test scores and OSCE performance in most assessed skills, including pulpotomy, tooth preparation, incision and suturing, and patient intake. Engagement scores were also significantly higher in the domains of emotional engagement and participation/interaction, and overall student satisfaction improved, particularly regarding teaching quality and student-centric learning methods. Word cloud analyses of student feedback revealed a stronger emphasis on collaboration, participation, and innovation in the TBL + PT cohort compared to the traditional group. Conclusions Incorporating Team-Based Learning and Peer Teaching into standardized dental residency training markedly enhanced theoretical knowledge, clinical proficiencies, and learner engagement. This instructional strategy improved residents’ technical competencies and cultivated stronger team collaboration, communication, and higher satisfaction levels, offering a promising alternative to traditional teaching for residency training in oral medicine.